Metodi e strategie didattiche in Higher Education per formare alla gestione delle dinamiche relazionali e comunicative. Il caso dei servizi educativi 0-6 di fronte all’emergenza da Covid-19 - Frison, Daniela (Rivista Italiana di Educazione Familiare, 2020)
The management of relational and communicative dynamics in a variety of educational and training contexts is recognized as a key element of both education and training courses for educators and educational services’ Quality Assurance processes. The paper widely reflects on educational and communicative dynamics in today’s world and educational settings and focuses on the exposure to global risks and the response to deal with the epidemiological Covid-19 emergency. Starting from the results of a multiple case study involving ECEC staff, the paper aims to figure out aligned strategies, teaching, and learning methods to embrace relational and communicative dynamics in the Higher Education classroom.